2017
DOI: 10.5807/kjohn.2017.26.1.30
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Psychosocial Work Environments on Depressive Symptoms among Korean Registered Nurses

Abstract: Results:The thirty-five percentage of Korean registered nurses reported the risk for depressive symptom. Korean nurses with higher 'work-family conflict' were more likely at the risk of depression almost 1.83 (95% CI 1.04~3.20) times than their counterpart. Higher 'possibilities for development' were more likely decrease almost 60% of the risk of depressive symptom. Conclusion: Work-family conflict and possibility of development were associated with depressive symptom among Korean registered nurses. We suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…Practices also had a significant correlation with the job stress of the correctional officers. This result is consistent with the results of a previous study [23], which showed that job stress had a significant influence on nurses' patient safety activities. In a situation in which COVID-19 is spreading nationwide, the correctional officers' degree of knowledge of the COVID-19-related rules of conduct, and of ways to implement them, will help to reduce the spread of infection among inmates and achieve safe management of the prison environment.…”
Section: Discussionsupporting
confidence: 93%
“…Practices also had a significant correlation with the job stress of the correctional officers. This result is consistent with the results of a previous study [23], which showed that job stress had a significant influence on nurses' patient safety activities. In a situation in which COVID-19 is spreading nationwide, the correctional officers' degree of knowledge of the COVID-19-related rules of conduct, and of ways to implement them, will help to reduce the spread of infection among inmates and achieve safe management of the prison environment.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that 524 of 1036 subjects were in the depressed group, accounting for 50.6% of all subjects. This figure was somewhat higher compared to a study of nurses using the WHO-5 Index, in which the proportion of those at risk for depression was 35.4% and a large-scale study of 50,032 subjects using data from the 3rd Korean Working Conditions Survey, in which 39.0% were at risk [ 18 , 19 ]. However, a study of male white-collar workers in an automobile company found that 57.7% had depressive symptoms [ 10 ], which might be related to differences in type of occupation or the workplace atmosphere.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, registered nurses suffer from depression at almost twice the rate of individuals working in other professions [3]. As nurses are the first point of contact most patients have in a clinic setting, and given that nurses comprise the highest percentage (68%) of health workers in Korea, their role is directly linked to the quality of medical service provided and received [4,5].…”
Section: Introductionmentioning
confidence: 99%